Gender disparity in maintenance hemodialysis units in South India: a cross-sectional observational study - Shankar, Mythri; Satheesh, Gouri; A., Kishan; C. G., Sreedhara; Reddy, Gireesh G (Frontiers in Nephrology, 2024)
BackgroundDiseases manifest differently according to gender in many medical specialties. However, sex differences in kidney diseases have not been well explored worldwide, especially in India. These differences could also be attributed to sociocultural factors. Although CKD is more prevalent in women worldwide, most men are initiated on kidney replacement therapy (KRT). This study aimed to examine sex disparities in patients on maintenance hemodialysis.Materials and methodsA cross-sectional observational study was conducted in two maintenance hemodialysis units at the Institute of Nephrourology, a tertiary care referral government center in Bengaluru, India. Demographic characteristics and laboratory parameters were also recorded.ResultsIn total, 374 adult patients (aged >18 years) were included in the study. Most patients (72.7%) were men. Mean age in men was 46.95 ± 12.65 years, and women was 46.63 ± 13.66 years. There was no significant difference in marital status and the availability of caretakers between the groups. Spouses were the predominant caretakers for both sexes (64% men and 51% women, P = 0.14). Sons cared more for patients with mother than fathers (19.6% vs 8.8%, P = 0.074). Diabetic nephropathy was the most common cause of ESKD in both groups (33.1% vs 31.3%, P = 0.92). Men had a significantly longer duration of HTN and received more HD sessions per week than women. Mean hemoglobin (9.9 ± 1.79 vs 9.46 ± 1.47 g%) and mean serum creatinine (7.76 ± 2.65 vs 6.41 ± 2.27 mg/dl) were higher in men compared to women (P <0.002). Intradialytic complications, such as hypotension and cramps, were significantly more common in women than in men (P = 0.004). Most men (47.1%) were planning a kidney transplant (and were waitlisted) compared with fewer women (43%). There was no significant difference in the average number of hospitalizations per month or HD vintage.ConclusionWomen tend to initiate dialysis later, and a lesser number are waitlisted for kidney transplantation, which might be partly related to varying access to or delivery of health care services. Factors such as lack of education, insufficient identification of and strategies to address cultural obstacles to healthcare, and a shortage of financial means to afford medical care are potentially correctable elements that might explain this discrepancy.